Forecasting Electrical Energy Loads at PT Krakatau Daya Electric Using the Linear Regression Method - Krisna Bayu; Dhea Rahmalia Henidar; Fahmi Hermastiandi; Galih Prasetya; Adi Nugraha (Journal of Mechatronics and Artificial Intelligence, 2024)
The importance of the role of electrical energy at this time cannot be denied and it is difficult to imagine how life would be without electricity, not only as a source of light at night in Cilegon City because it is rich in resources, especially in the industrial sector. Therefore, the existence of a guaranteed power supply is very important. PT Krakatau Daya Listrik, as the main provider and distributor of electrical energy in the KIEC Area (Krakatau Industrial Estate Cilegon), indirectly becomes the backbone for the economy of the people in the trading area of PT Krakatau Daya Listrik. The method used in making predictions is the linear regression method which is a method to test how accurate the relationship between x and y is. In addition, to do forecasting or similarity testing, use Google Colab. The results of the two show a correlation coefficient of 0.4 which is enough to have a relationship between x and y, the more years the more power or electrical energy is needed. This is very relevant considering that electrical energy has become a necessity, so this forecast can help electricity service providers to meet consumer needs.